Implementation Of Un Peacekeeping New Model To Enhance Konga Support For Garuda Task Force Unifil: English - Sidik Purnomo; Ferdinand Hasudungan Siagian; Oktaheroe Ramsi (International Journal Of Humanities Education and Social Sciences (IJHESS), 2026)
Indonesia’s participation in the United Nations Interim Force in Lebanon (UNIFIL) demonstrates its strong commitment to international peacekeeping while functioning as a key instrument of defense diplomacy. Nevertheless, an evolving security environment and the requirements of implementing the United Nations Peacekeeping Operations (UN PKO) New Model demand a high degree of operational preparedness from the Garuda Contingent. This study seeks to examine the operational readiness of Satgas Garuda, evaluate the application of UN PKO New Model principles, and analyze their strategic implications for Indonesia’s defense diplomacy. A qualitative descriptive approach is employed, utilizing in-depth interviews, document review, and a SWOT analysis supported by IFAS–EFAS matrices. The results indicate that Satgas Garuda’s operational readiness is classified as high, driven by professionalism, discipline, and well-structured pre-deployment training, although challenges persist in logistical support and communication interoperability. The UN PKO New Model has been effectively implemented through CIMIC initiatives, compliance with international legal frameworks, and adaptive engagement with local contexts. From a strategic perspective, the achievements of Satgas Garuda contribute to enhancing Indonesia’s global standing and reinforcing its role in international defense diplomacy